2017
DOI: 10.1016/j.annemergmed.2017.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Association of Out-of-Hospital Hypotension Depth and Duration With Traumatic Brain Injury Mortality

Abstract: Background Out-of-hospital hypotension has been associated with increased mortality in traumatic brain injury (TBI). The association of TBI mortality with the depth or duration of out-of-hospital hypotension is unknown. Methods We evaluated adults and older children with moderate/severe TBI in the pre-implementation cohort of Arizona’s statewide Excellence in Prehospital Injury Care (EPIC) Study. We used logistic regression to determine the association between the depth-duration dose of hypotension [depth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 49 publications
(53 reference statements)
0
49
0
1
Order By: Relevance
“…Arterial hypotension, (systolic blood pressure <90 mmHg), was an identified prehospital risk factor for mortality [48]. A study of major traumatic brain injury found that the depth, and duration of out-of-hospital hypotension were strongly associated with increased mortality [49]. Hypothermia (temperature <35 °C) was also identified as a prehospital risk factor for mortality [48,50].…”
Section: Prehospital and Emergency Carementioning
confidence: 99%
“…Arterial hypotension, (systolic blood pressure <90 mmHg), was an identified prehospital risk factor for mortality [48]. A study of major traumatic brain injury found that the depth, and duration of out-of-hospital hypotension were strongly associated with increased mortality [49]. Hypothermia (temperature <35 °C) was also identified as a prehospital risk factor for mortality [48,50].…”
Section: Prehospital and Emergency Carementioning
confidence: 99%
“…Prehospital interventions that mitigate secondary injury from hypotension, hypoxia, and hypocarbia have also been shown to improve TBI outcomes. 11,[18][19][20] Preliminary, unadjusted subgroup analysis in the PAMPer trial suggested a survival benefit in patients with severe head injury, as defined by Abbreviated Injury Severity (AIS) scores for the head. 8 However, to our knowledge, the association of early plasma administration with survival has not been fully characterized in the subgroup of patients with TBI as confirmed by computed tomography (CT) while adjusting for potential confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, severely brain-injured patients may benefit from early neurosurgical intervention. Although it has been shown that early physiological stabilization to avoid hypoxia, hypotension, and hypo-and hypercarbia led to improved outcomes from TBI, [34][35][36] the optimum time window for neurosurgical intervention in patients with TBI remains uncertain.…”
mentioning
confidence: 99%